THERE ARE MALE TEARS IN THAT COMMENT SECTION. THE DISCURSIVE NEGOTIATION OF MASCULINITY IN ITALIAN ONLINE MEN’S GROUPS - Farci, Manolo (AoIR Selected Papers of Internet Research, 2020)
Despite the consolidation of works on the heterogeneous nature of the so-called Manosphere, a lot of these studies consider masculinity as an overall governing force of men’s behaviors. This is has led to overlooking how subject positioning is always negotiated in multiple and contradictory discourses that are not easily captured by structurally oriented frameworks such as hegemonic or toxic masculinity. By focusing on the recent third development in men’s critical studies of masculinity, this work seek to investigates the discursive construction of masculinity in digital environment, in order to identify the various resources, in the form of established repertoires, that men use to position themselves in relation to conventional discourses of the masculine, and how masculinity both impinges upon and is transformed by those practices. Using a qualitative methodology, we analyze the content of two Facebook Pages dedicated to men’s rights issues, called Antisessismo (Antisexism) and Diritti Maschili – Equità e Umanità (Men’s rights – Equity and Humanity). Our findings suggest that in these groups, masculinity is rarely negotiated or discussed but it is assumed as a common sense, providing a basis for shared social understandings. However, there is no unitary meaning to this common sense of masculinity, on the contrary, it contains many contradictory or competing arguments. Individuals are positioned by discourses, but, as our data demonstrate, these identity positions are by no means stable and consistent: users can shift between different modes of masculinity and actively re-create positions for themselves, especially in response to “trouble”.